The Influence of Toll Laut Ship on Seaweed Eucheuma Cottoni Trade in Nunukan Border Area - Basran; Herlina; Harianti; Helena, Wilybroda (Future Science, 2024)
This study discusses (1) The Positive Impact of the Sea Toll (2) The Bene-fits for Seaweed Swordsmen. The research method used in this study is qualitative, which produces primary data and secondary data. This data collection technique is using observation and documentation techniques. The results of this study show (1) the potential impact of the sea toll pro-gram for entrepreneurs in sending dried seaweed crops outside the city of Nunukan for production, the negative impact of the sometimes erratic sea toll ship jadawal makes some entrepreneurs choose to use private ships even though the price is more expensive. (2) Benefits of sea tolls for seaweed traders Better accessibility: With a connected sea route, mer-chants can send their seaweed products to domestic and international markets faster and more smoothly. Lower transportation costs: seaweed entrepreneurs in Nunukan Regency can reduce their transportation costs. This can increase the competitiveness of seaweed products and provide financial benefits for traders.